Effect of a Humanized Diet Profile on Colonization Efficiency and Gut Microbial Diversity in Human Flora-Associated Mice - Dong, Sashuang; Zeng, BenHua; Hu, Ling; Zhang, Yuling; Xiong, Jiaqi; Deng, Jing; Huang, Liyan; Liao, ZhenLin; Wang, Jie; Wei, Hong; Fang, Xiang (Frontiers in Nutrition, 2021)
The human flora-associated (HFA) mice models establishment allows us to design interventions impossible in human diseases researches that test specific hypotheses and explore the complex commensal microbiome, avoiding the ethical limitations of using humans directly to study intestinal flora disease models. However, few studies have investigated the effect of the humanized diet profile—coarse feed diet (CFD) on colonization efficiency and gut microbial diversity in HFA mice. In this study, we tested the colonization efficiency and gut microbial diversity in Germ-free KM mice with CFD and purified feed diet (PFD) at different time (1, 2, 4 weeks). As a result, although the colonization efficiency was significantly difference (67.50%–70% vs 72.69%-85.96%) in HFA mice, the colonization efficiency of HFA mice fed the PFD (85.96%) was significantly higher than the CFD (69.61%) at 2 weeks, meanwhile, fed the PFD (72.69%) was comparable to the microbiota of HFA mice fed the CFD (70%) at 4 weeks. Moreover, the gut microbial diversity of HFA mice fed the CFD was similar to the human species. In addition, HFA mice of feeding CFD was closer to that of human than PFD about KEGG pathways of colonic microbiota metabolic pathways, including amino sugar and nucleotide sugar metabolism, biosynthesis of amino acid, carbon metabolism, purine metabolism, and phosphotransferase systems (PTS). It was concluded that the humanized diet profile——CFD and PFD could support the establishment of a human microbiota in mice. Furthermore, constructing HFA mice models of feeding the CFD at 4 weeks may be more suitable for research on human-derived intestinal diseases.